Analysis of the Impact of Corporate Social Responsibility on Corporate Competitiveness - Sun, Yi (International Journal of Global Economics and Management, 2024)
In today's societal context, corporate development faces new opportunities and challenges, with competition among businesses shifting from talent, products, and economic strength to corporate social responsibility (CSR). This change brings new demands for business development. CSR originated in Western countries, but initially did not significantly impact corporate growth. In recent years, the concept of social responsibility has gradually been recognized by society and has gained influence internationally. Current research, both domestically and internationally, mainly focuses on how CSR fulfillment affects corporate competitiveness. To maintain a strong position in the highly competitive market, companies must actively fulfill their social responsibilities. Only by doing so can they gain customer recognition and wield better market influence. Therefore, this paper comprehensively analyzes the impact of CSR on corporate competitiveness, clarifies the role of CSR in enhancing market competitiveness, and ensures that companies actively fulfill social responsibilities while developing economically.